Physiological and proteomic analyses of leaves from the halophyte Tangut Nitraria reveals diverse response pathways critical for high salinity tolerance - Cheng, Tielong; Chen, Jinhui; Zhang, Jingbo; Shi, Shengqing; Zhou, Yanwei; Lu, Lu; Wang, Pengkai; Jiang, Zeping; Yang, Jinchang; Zhang, Shougong; Shi, Jisen (Frontiers in Plant Science, 2015)
Soil salinization poses a serious threat to the environment and agricultural productivity worldwide. Studies on the physiological and molecular mechanisms of salinity tolerance in halophytic plants provide valuable information to enhance their salt tolerance. Tangut Nitraria is a widely distributed halophyte in saline–alkali soil in the northern areas of China. In this study, we used a proteomic approach to investigate the molecular pathways of the high salt tolerance of T. Nitraria. We analyzed the changes in biomass, photosynthesis, and redox-related enzyme activities in T. Nitraria leaves from plant seedlings treated with high salt concentration. Comparative proteomic analysis of the leaves revealed that the expression of 71 proteins was significantly altered after salinity treatments of T. Nitraria. These salinity-responsive proteins were mainly involved in photosynthesis, redox homeostasis, stress/defense, carbohydrate and energy metabolism, protein metabolism, signal transduction, and membrane transport. Results showed that the reduction of photosynthesis under salt stress was attributed to the down-regulation of the enzymes and proteins involved in the light reaction and Calvin cycle. Protein–protein interaction analysis revealed that the proteins involved in redox homeostasis, photosynthesis, and energy metabolism constructed two types of response networks to high salt stress. T. Nitraria plants developed diverse mechanisms for scavenging reactive oxygen species in their leaves to cope with stress induced by high salinity. This study provides important information regarding the salt tolerance of the halophyte T. Nitraria.